Bortezomib-induced thrombotic thrombocytopaenic purpura. (1st August 2012) - Mehta, Neha; Saxena, Ashish; Niesvizky, Ruben
Abstract : Thrombotic thrombocytopaenic purpura (TTP) is a thrombotic microangiopathy characterised by haemolytic anaemia, schistocytes on peripheral blood smear and thrombocytopaenia that can additionally present with fever, renal insufficiency and/or neurological abnormalities. While our understanding of idiopathic TTP has significantly advanced, there are still many unanswered questions regarding the pathophysiology of secondary TTP, which can be associated with malignancy, pregnancy, HIV infection, bone marrow transplantation and exposure to certain drugs including several chemotherapeutic agents. Here we present a case of bortezomib-associated TTP. Our patient developed microangiopathic haemolytic anaemia, thrombocytopaenia and altered mental status after her ninth dose of bortezomib. The drug was subsequently discontinued and the patient underwent one session of plasma exchange with clinical improvement and recovery of her platelet counts, disappearance of schistocytes and resolution of both neurological symptoms and haemolysis in 2 days.